Development Prospect of Aloe Vera Plant in Peatlands in West Kalimantan - Tommy Purba; Juliana C Kilmanun (Center for Journal Management and Publication, 2016)
Peat soil is one of the decent growing medium for aloe vera plant. Seeing the potential of peat land in West Kalimantan is quite extensive, this plant is cultivated commercially and becomes one of the leading commodity in peatlands in West Kalimantan, especially in Pontianak City with an area of more than 25,000 ha. With complete and varied nutrient content, this plant progress opportunities, especially for diversification is enormous ranging from food products and beverages such as juices, cocktails, aloe vera gel in syrup, jams, jellies, tarts, sweets, tea, chips and as well as agro-tourism in West Kalimantan. Existing obstacles now are market share and unstable price, trouble controlling plant diseases and peat area is flooded during the rainy season. Prospects for the future development of these plants can be carried out through the cooperation of government and relevant stakeholders,stable markets and prices, the acceleration of product promotion through fairs and business gathering activities, as well as the dissemination and application of cultivation technology and post-harvest of aloe vera.